Quantum metamaterials: Applications in quantum information science - Solomon Uriri; Yaseera Ismail; Mhlambululi Mafu (APL Quantum)
Metamaterials are a class of artificially engineered materials with periodic structures possessing exceptional properties not found in conventional materials. This definition can be extended when we introduce a degree of freedom by adding quantum elements such as quantum dots, cold atoms, Josephson junctions, and molecules, making metamaterials highly valuable for various quantum applications. Metamaterials have been used to achieve invisibility cloaking, super-resolution, energy harvesting, and sensing, among other applications. Most of these applications are performed in the classical regime. Metamaterials have gradually made their way into the quantum regime since the advent of quantum computing and quantum sensing and imaging. Quantum metamaterials are a relatively new technology, and their use in quantum information processing has proliferated. We restrict this study to quantum state manipulation and control, quantum entanglement, single photon generation, quantum state switching, quantum state engineering, quantum key distribution, quantum algorithms, orbital angular momentum, and quantum imaging. Considering these developments, we examine the theory, fabrication, and applications contributing to quantum information processing and how quantum metamaterials contribute to this field. We find that the ability to harness the unique properties of metamaterials to drive these applications is of great importance, as they have the potential to unlock new possibilities for revolutionizing quantum information processing, bringing the world closer to practical quantum technologies with unprecedented capabilities. We conclude by suggesting possible future research directions.